Transient beam-loading model and compensation in Compact Linear Collider main linac - O. Kononenko; A. Grudiev (Physical Review Special Topics. Accelerators and Beams, 2011)
A new model to compensate for the transient beam loading in the CLIC main linac is developed. It takes into account the CLIC specific power generation scheme and the exact 3D geometry of the accelerating structure including couplers. A new method of calculating unloaded and loaded voltages during the transient is proposed and a dedicated optimization scheme of the rf pulse to compensate the transient beam-loading effect is presented. It is demonstrated that the 0.03% limit on the rms relative bunch-to-bunch energy spread in the main beam after acceleration can be reached. The optimization technique has been used to increase the rf to beam efficiency while preserving the CLIC requirements and to compensate for the energy spread caused by the Balakin-Novokhatski-Smirnov damping and transient process in the subharmonic buncher. Effects of charge jitters in the drive and main beams are studied. It is shown that within the 0.1% CLIC specification limit on the rms spread in beams charge the energy spread is not significantly affected.